Islamic Education Policy in the Reform Era: Towards a More Progressive System - Alya Mardatillah B; Rezzi Yanti Naimah; Asmuri; Muhammad Darimus (al-Afkar, Journal For Islamic Studies, 2026)
This study examines Islamic education policy in Indonesia during the Reformation era, highlighting the transformation from a centralized to a decentralized system, strategic policies, progress, and challenges faced. Islamic education gained strong legitimacy within the national education system through Law Number 20 of 2003, which expanded recognition of various Islamic educational institutions. Furthermore, strategic policies such as the allocation of 20% of the state budget (APBN), compulsory education programs, and the development of competency-based curricula have had a positive impact. However, challenges such as regional disparities and radicalism remain a concern. This study emphasizes the importance of innovation and inclusivity to ensure Islamic education remains relevant in the era of globalization.